Kombinasi Dosis Pupuk Urea dan POC terhadap Pertumbuhan Vegetatif Padi Skala Rumah Kaca: Combination of Urea Fertilizer Doses and Liquid Organic Fertilizer on Vegetative Growth of Rice in Greenhouse Scale - Muhammad Nasrul; Nur Isra; Dwi Wahyuni Haswin; Ilham; Muhammad Isbahuddin; Hikmawati; Nilu Langsari (Universitas Hasanuddin, 2026)
Dryland areas in Indonesia offer substantial potential for increasing rice production; however, their productivity is often limited by low soil organic matter caused by the continuous use of chemical fertilizers. One possible approach to address this issue is the application of liquid organic fertilizers derived from plant residues, such as gamal (Gliricidia sepium) and lamtoro (Leucaena leucocephala) leaves, which are expected to improve soil properties and support plant growth. This study aimed to examine the vegetative response of Mikongga rice to different application rates of liquid organic fertilizers, applied either alone or in combination with urea, under dryland conditions. Experiment was conducted from September to November 2025 in Majene Regency, West Sulawesi, using a factorial randomized block design with 12 treatment combinations and threee replications. Observed variables included plant height, number of tillers, and selected soil properties such as pH, moisture content, and temperature. The results revealed that the application of liquid organic fertilizers, either individually or combined with urea, did not significantly affect plant height or tiller number during the observation period of 28 to 49 days after planting. In addition, no significant changes were observed in soil characteristics. These findings indicate that the applied fertilizer rates were insufficient to enhance plant growth or improve soil conditions, suggesting the need for further studies with higher dosages or alternative application methods.